2023
DOI: 10.1186/s13021-023-00226-0
|View full text |Cite
|
Sign up to set email alerts
|

Thinning effects on stand growth, carbon stocks, and soil properties in Brutia pine plantations

Abstract: Background The purpose of this study was to investigate the effects of thinning on stand growth, carbon (C) sequestration, and soil properties in Brutia pine (Pinus brutia Ten.) plantations. The study was conducted at two experimental sites -the Antalya-Kaş and Isparta-Eğirdir plantation areas- in Turkey between 1985 and 2015. Different thinning intensities -unthinned (control), moderate, and heavy- were replicated in four blocks. We determined the C in the living biomass, litter, soil, and som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Living plants, through photosynthetic processes, transform CO 2 to biomass by dissipating the carbon in the atmosphere and reserving it in the plant tissues and soils [12,13]. In agricultural or forest ecosystems, the generated biomass is specifically stocked as aboveground biomass (AGB), belowground biomass (BGB), dead wood, litter, and soil organic matter [14][15][16]. Forest plants and forest ecosystems including soils are key carbon sinks and sources [17][18][19][20][21] and have significant impacts on the realization of many sustainable development goals (SDGs), especially SDG 1, SDG 2, SDG 3, SDG 6, SDG 7, SDG 11, SDG 12, SDG 13, and SDG 15 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Living plants, through photosynthetic processes, transform CO 2 to biomass by dissipating the carbon in the atmosphere and reserving it in the plant tissues and soils [12,13]. In agricultural or forest ecosystems, the generated biomass is specifically stocked as aboveground biomass (AGB), belowground biomass (BGB), dead wood, litter, and soil organic matter [14][15][16]. Forest plants and forest ecosystems including soils are key carbon sinks and sources [17][18][19][20][21] and have significant impacts on the realization of many sustainable development goals (SDGs), especially SDG 1, SDG 2, SDG 3, SDG 6, SDG 7, SDG 11, SDG 12, SDG 13, and SDG 15 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Soil active organic carbon is an important part of soil organic carbon, which can reflect the sensitivity of the soil carbon pool. The plant community injects photosynthally fixed organic carbon into soil through litter, turnover of fine roots, and root exudates [ 39 , 40 ]. The quantity and quality of litter transported to the soil by different vegetation types and the root exudates were different, resulting in significant differences in soil active carbon components (MBC, EOC, DOC, and POC) in different soil layers of different plant communities [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Erkan et al in Brutia pine plantations, evidenced that C stocks in the litter, and soil were not significantly influenced by the thinning intensity [39]. The nutrients in the litter and soil, and other soil properties, were not significantly different among thinning parcels.…”
Section: Thinning Time Effects On Soil Chemical and Biochemical Prope...mentioning
confidence: 93%
“…Findings from Settineri et al [20], revealed that high thinning intensity had the most significant impact on increasing the stable fraction of soil organic matter (SOM) and the humification ratio. This indicates a higher degree of humification and a greater CEC [39]. Ma et al highlight that the specific effects of thinning intensity on soil chemical properties can vary based on factors such as initial soil conditions, tree species, climate, and site management practices [15].…”
Section: Thinning Intensity Effects On Soil Chemical and Biochemical ...mentioning
confidence: 99%